Solution;

P(x, y) $$\rightarrow$$ P'(x, -y)

$$\therefore$$ A(1, 3) $$\rightarrow$$ A'(1, -3)

B(4, 5) $$\rightarrow$$ B'(4, -5) and

C(6, 2) $$\rightarrow$$ C'(6, -2)

$$\triangle$$ABC and its image $$\triangle$$A'B'C' are shown on the graph.

Solution;

P(x, y) $$\rightarrow$$ P'(-x, y)

$$\therefore$$ A(2, 3) $$\rightarrow$$ A'(-2, 3)

B(4, 5) $$\rightarrow$$ B'(-4, 5) and

C(6, 2) $$\rightarrow$$ C'(-6, 2)

$$\triangle$$ABC and its image $$\triangle$$A'B'C' are shown on the graph.

Solution;

P(x, y) $$\rightarrow$$ P'(x, -y)

$$\therefore$$ P(3, 1) $$\rightarrow$$ P'(3, -1)

Q(5, 4) $$\rightarrow$$ Q'(5, -4) and

R(2, 6) $$\rightarrow$$ R'(2, -6)

$$\triangle$$PQR and its image $$\triangle$$P'Q'R' are shown on the graph.

Solution:

P(x, y) $$\rightarrow$$ P'(x, -y)

$$\therefore$$ A(-4, 5) $$\rightarrow$$ A'(-4, -5) and

B(6, -2) $$\rightarrow$$ B'(6, 2)

Line AB and its image A'B' are shown on the graph.

Solution;

P(x, y) $$\rightarrow$$ P'(-x, y)

$$\therefore$$ X(1, 3) $$\rightarrow$$ X'(-1, 3) and

Y(4, 5) $$\rightarrow$$ Y'(-4, 5)

Line XY and its image X'Y' are shown on the graph.

Solution:

P(x, y) $$\rightarrow$$ P'(x, -y)

$$\therefore$$ A(-5, -2) $$\rightarrow$$ A'(-5, 2) and

B(2, 3) $$\rightarrow$$ B'(2, -3)

Line AB and its image A'B' are shown on the graph.

Solution:

P(x, y) $$\rightarrow$$ P'(-x, y)

$$\therefore$$ A(-5, -2) $$\rightarrow$$ A'(5, -2) and

B(2, 3) $$\rightarrow$$ B'(-2, 3)

Line AB and its image A'B' are shown on the graph.

Solution:

Let AB be the given point, then

A(3, 4) and B (8, 10)

P(x, y) $$\rightarrow$$ P'(-x, y)
$$\therefore$$ A(3, 4) $$\rightarrow$$ A'(-3, 4) and
B(8, 10) $$\rightarrow$$ B'(-8, 10)